Clinical isolates of Anantapuramu for the protein E isolation of the dengue virus - C M Anuradha, K. Chandravathi, Gangadharam Poli, Suresh Kumar Chitta, Madhusudana Pulaganti, Prasad Reddy S Hari, Chandraprakash Chinta (Journal of Advanced Zoology, 2022)
In theclinical samples from the state of Anantapuramu, the dengue virus serotype 2 protein E gene was found. It was established that the protein E gene was present in the models by using RT-PCR and cellular isolates. There has been one new sub strain discovered that are akin to the hermits described in previous investigations. An investigation of the epidemiology of the isolated strain was conducted using a phylogenetic analysis of the strain.